Hubungan Tingkat Pengetahuan Terhadap Perilaku Pencegahan Covid-19 Santri Di Pondok Pesantren - Dyah Restuning Prihati; Cahyani Setianingrum; Dwi Retnaningsih (Malahayati Nursing Journal, 2022)
ABSTRACT Coronavirus Disease of 2019 is a group of alphacoronavirus and betacoronavirus viruses that often cause colds and other mild upper respiratory tract infections in the human body. The role of Islamic boarding schools in the preventive and promotive efforts of COVID-19 by following the rules from the government for safe activities during the pandemic and the provision of infrastructure in the pesantren environment. Objective to find out the relationship between the level of knowledge and behavior of students in the prevention of COVID-19 in Islamic boarding schools. This study used a descriptive design with a cross-sectional study approach, which was to find a relationship between the level of knowledge and the COVID-19 prevention behavior of students in Islamic boarding schools. Sampling with solving sampling technique. The research time is 1 month in 2021 with the location at the APIK Demak Islamic boarding school. The inclusion criteria are students who are teenagers (11-19 years old) and have not received counseling about COVID-19. While the exclusion criteria are bat students who do not stay overnight in the cottage. The instrument uses a knowledge questionnaire about COVID-19 using the Guttman scale and a student behavior questionnaire in preventing COVID-19 with a Likert Scale. The results of this study showed that most respondents showed a good level of knowledge with negative behavior as many as 24 people. The significance value is 0.038 which indicates that there is a significant correlation between the level of knowledge and the attitude of the respondents. The gamma correlation value of 1,000 indicates that the correlation in the positive direction with the strength of the correlation is very strong. There is a relationship between the level of knowledge on the COVID-19 prevention behavior of students in Islamic boarding schools. It is hoped that pesantren administrators can further facilitate the need for information on health education regarding the prevention of COVID-19. Keywords: Knowledge, Behavior, Prevention of COVID-19, Santri ABSTRAK Coronavirus Disease of 2019 adalah sekelompok virus alphacoronavirus dan betacoronavirus yang sering menyebabkan pilek dan infeksi saluran pernapasan atas ringan lainnya di tubuh manusia. Peran pesantren dalam upaya preventif dan promotif COVID-19 dengan mengikuti aturan dari pemerintah beraktivitas yang aman selama pandemi dan pengadaan sarana-prasarana di lingkungan pesantren. Tujuan untuk mencari hubungan tingkat pengetahuan dan perilaku santri terhadap pencegahan COVID-19 di pondok pesantren. Penelitian ini menggunakan desain deskriptif dengan pendekatan cross sectional study, yaitu mencari hubungan tingkat pengetahuan terhadap perilaku pencegahan COVID-19 santri di pondok pesantren. Pengambilan sampel dengan teknik slovin sampling. Waktu penelitian selama 1 bulan pada tahun 2021 dengan lokasi di pondok pesantren APIK Demak. Kriteria inklusi yaitu santri dengan usia remaja (11-19 tahun), belum mendapatkan penyuluhan tentang COVID-19. Sedangkan kriteria Eksklusi yaitu santri kalong yang tidak  tinggal menginap di pondok. Instrumen menggunakan kuesioner pengetahuan tentang COVID-19 dengan menggunakan skala Guttman dan kuesioner perilaku santri dalam pencegahan COVID-19 dengan skala Likert Scale. Hasil penelitian ini terdapat responden terbanyak menunjukkan tingkat pengetahuan baik dengan perilaku negatif sebanyak 24 orang. Nilai significancy 0,038 yang menunjukkan bahwa ada korelasi antara tingkat pengetahuan dengan sikap responden yang bermakna. Nilai korelasi gamma sebesar 1,000 menunjukkan bahwa korelasi arah positif dengan kekuatan korelasi sangat kuat.  Terdapat hubungan tingkat pengetahuan terhadap perilaku pencegahan COVID-19 santri di pondok pesantren. Diharapkan agar pengurus pesantren dapat lebih memfasilitasi kebutuhan informasi edukasi kesehatan tentang pencegahan COVID-19.Kata kunci: Pengetahuan, Perilaku, Pencegahan COVID-19, Santri